Clinical classification of tooth position in the alveolar bone housing with periodontal defects - Yoshiaki Hasegawa; Tadahiro Takayama; Yoshihiro Iwano (Elsevier, 2021)
A new classification of tooth position in the alveolar bone housing, which indicates the width of alveolar bone for buccolingual direction, with bone defects caused by periodontal disease is proposed. This classification highlights the importance of tooth position in the alveolar bone housing in terms of the progression of the regenerative process and the factors that may affect the prognosis of compromised teeth after regenerative surgery. Tooth positions were divided into two groups: (i) The whole tooth is centrally positioned in the existing alveolar bone housing (Grade I) and (ii) A part of the tooth is exposed out of the existing alveolar bone housing (Grade II). Grade II is further divided into two subgroups according to situations encountered in clinical practice. The following subclasses are suggested: Subgroup A, where the alveolar bone housing is broader than the tooth, and Subgroup B, where the alveolar bone housing is narrower than the tooth. These subgroups represent a discrepancy between tooth size and alveolar bone dimensions in the buccolingual orientation. This classification could be useful for planning the correct regenerative treatment for each type of the tooth position in the alveolar bone housing with periodontal defects.